Perlindungan Hukum Bagi Korban Tindak Pidana Pencabulan Terhadap Anak Laki-Laki (Studi Kasus Di Kepolisian Resort Kota Surakarta) - PATTY, HERMA ERA, Muchamad Iksan, S.H., M.H, Bambang Sukoco, S.H., M.H (2015)
This study aims to determine the form of legal protection, the implementation of protection and barriers that arise in the implementation of legal protection for children as victims of criminal acts of abuse at the Police Surakarta. The research method with empirical juridical approach that is descriptive qualitative. Sources of data include secondary and primary data. Methods of data collection done in 2 stages: primary data collection through interviews and secondary data collection methods literature. The results showed that the forms of legal protection are legally regulated in specific legislation for children namely Law No. 35 of 2014 amendments to the Law No. 23 of 2002 on Protection of Children and the implementation of legal protection has not been done optimally because they still use laws -undangan long that Act No. 23 of 2002 on Child Protection. While inhibiting factor among other factors in the implementation of law, law enforcement officers factors, factors of facilities and support facilities, community factors, and cultural factors.